Dermoscopy of Early-Stage Mycosis Fungoides: Comparative Study with Inflammatory Dermatoses - Amel Chabbouh; Noureddine Litaiem; Houda Hammami; Mourad Mokni; Faten Zeglaoui (Dermatology Practical & Conceptual)
Introduction: The diagnosis of early-stage mycosis fungoides (MF) is challenging often requiring multiple biopsies and may be confused with plaque psoriasis (PP) and chronic dermatitis (CD).